Optimalisasi Branding Media Sosial dalam Meningkatkan Citra dan Minat Calon Peserta Didik di SMP Islam Al Jihad, Johar Baru - Ade Firmansyah; Noviandari Sari Utami; Eka Rofiyanti (Institut Ilmu Sosial dan Manajemen STIAMI, 2026)
This study aims to analyze social media branding strategies in enhancing the image and attractiveness of SMP Islam Al Jihad. The research employed a descriptive qualitative approach, with data collected through in-depth interviews, observations, and documentation. Data were analyzed using domain, taxonomic, and componential analysis techniques.The findings indicate that the school's social media branding strategy begins with developing a strong institutional identity, creating informative, educational, and Islamic value-based content, and managing social media platforms consistently. The implementation includes publishing academic activities, students' achievements, flagship programs, and religious events to build a positive image and strengthen public trust. Social media branding has become the primary factor in enhancing the school's reputation, expanding its public outreach, and increasing prospective students' interest in enrolling at SMP Islam Al Jihad. Supporting factors include the commitment of school stakeholders, effective teamwork, and the availability of information technology facilities. Meanwhile, the main challenges are limited human resources with digital branding expertise, budget constraints for promotional activities, unstable internet connectivity, and the relatively low level of digital literacy among some members of the community. Keywords Selling Price, Brand Image, Purchase Interest, TikTok Shop, Luxcrime Cosmetics